Impact of cleaner production practices in the nigerian wood industry on sustainability and environmental performance (2023)
Wood residues generated in Nigeria amount to approximately 5.2 million tonnes annually, highlighting the resource-intensive nature of the Nigerian wood industry. Cleaner production practices, which involve the identification and implementation of strategies to reduce raw material consumption, energy use, waste generation, and pollution, have been widely adopted in many countries. However, in Nigeria, the adoption of cleaner production practices remained limited. This study aims to review the potential impact of cleaner production practices in the Nigerian wood industry on productivity and the creation of a sustainable environment. It sheds light on the unique characteristics and challenges faced in the Nigerian wood industry that influence the widespread adoption of cleaner production practices. The study delved into the different phases of cleaner production implementation, emphasizing the importance of planning, implementation, monitoring, and evaluation. It highlighted the adoption of low-cost and practical cleaner production measures, debunking the misconception that cleaner production implementation is always costly. Furthermore, the study examined the prospects and challenges of implementing cleaner production measures within the specific context of Nigeria's peculiarities. It discussed comprehensive waste management strategies, noise control measures, materials modification, and substitution, as well as the application of cleaner production practices on machinery and equipment. The paper emphasised the need for stronger policies and their enforcement to ensure compliance with cleaner production practices in the wood industry. By promoting the adoption of cleaner production measures, the country can witness enhanced productivity, minimise waste, and create a sustainable and environmentally friendly wood industry sector.